Implementation of Assessment for Learning-Oriented Student Worksheets to Improve Students’ Thermochemistry Learning Outcomes - Orisia Toriqotul Ulum; Muchlis Muchlis; Maharani Agustina Arivi (Jurnal Pendidikan Sains Indonesia, 2026)
Thermochemistry is considered difficult because students need to connect abstract concepts, experimental observations, and calculation procedures in one learning process. Therefore, structured learning support that provides learning targets, feedback, and reflection is needed. This study focused on describing how students’ thermochemistry learning outcomes increased after the use of assessment for learning-oriented student worksheets. A pre-experimental approach using a one-group pretest-posttest design was carried out, with 24 students of class XI-B at SMA 1 Muhammadiyah Taman as participants. The learning process was carried out over two meetings covering system and surroundings, exothermic and endothermic reactions, thermochemical equations, calorimetry, and heat calculation. Data were collected through pretest and posttest, observation sheets for teacher and student activity, and student response questionnaire. The data were analyzed using rate (percentage) analysis, a normality test, the Wilcoxon signed-rank test, and N-gain. The findings indicated that teacher activity reached 91.54% and student activity reached 89.69%, both in the very good category. Students’ mean score improved from 60.94 to 85.83, indicating that the difference between the pretest and posttest results was significant. The N-gain result was categorized as medium with a mean score of 0.63, whereas students’ responses were categorized as very good with a rate of 97.92%. These results show that assessment for learning-oriented student worksheets can enhance students’ thermochemistry learning outcomes